IMPLEMENTASI REFORMASI ADMINISTRASI BIDANG PENDIDIKAN DAN KESEHATAN DI KABUPATEN BANYUWANGI - Herwin Kurniadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2026)
Administrative reform in education and health is a critical prerequisite for improving public service quality and human development at the local level. This study aims to analyse the implementation of administrative reform in Banyuwangi Regency with reference to three main strategies: procedural, technical, and programmatic reform. The research employed a descriptive qualitative approach through in-depth interviews with key informants from education and health offices, community representatives, and private sector partners, complemented by direct field observation and extensive document review. The findings indicate that procedural reform expanded community and private sector participation through inclusive education regulations, reduced dropout rates, and health insurance schemes for the poor. Technical reform was realised through Banyuwangi Digital Society, Smart Kampung, e-education, and e-health, which improved bureaucratic efficiency and transparency. Meanwhile, programmatic reform delivered innovations such as Banyuwangi Cerdas, accelerated stunting reduction, extended expected years of schooling, and community-based health services, contributing to a notable rise in the Human Development Index. In conclusion, administrative reform in Banyuwangi has successfully built an adaptive, collaborative, and digital-based governance model for sustainable public services. The research contributes an integrative framework for synergising the three reform strategies to achieve innovative, accountable, and equitable local governance